Deep-sea microbially influenced corrosion and biomineralization - Ge, Yanchen; Wang, Can; Etim, Ini-Ibehe Nabuk; Khan, Sikandar; Li, Chengpeng; Yang, Luhua; Liu, Jia; Yi, Peijia; Liu, Jiazhi; Sand, Wolfgang; Zhang, Ruiyong (Frontiers in Microbiology, 2025)
Microbially influenced corrosion (MIC) and biomineralization are widely observed in marine, deep-sea, freshwater, and soil ecosystems. Recently, MIC and biomineralization associated with biofouling have significantly impacted marine resources, including deep-sea minerals and organisms. Notably, uncontrolled biomineralization by certain microorganisms, such as barnacles adhering to ship hulls, can lead to structural damage and economic challenges due to biocorrosion. Biomineralization can be categorized into induced mineralization and controlled mineralization. In natural environments, induced biomineralization is the predominant process. The mechanisms of induced biomineralization and MIC in extreme deep-sea environments have attracted significant attention. The factors influencing these processes are highly complex. The microbial-material interfaces serve as the primary sites for key biochemical reactions driving biocorrosion and biomineralization. Within these interfaces, biofilms, their secreted extracellular polymers, and extracellular electron transfer mechanisms play crucial roles in these processes. Thus, a comprehensive understanding of MIC and biomineralization under deep-sea environmental conditions is essential. Investigating the relationship between these phenomena and exploring their underlying mechanisms are critical for both research advancements and industrial applications.